The pyramid of game design designing, producing and launching service games - Lovell, Nicholas (CRC Press, Taylor & Francis Group, 2019)
Game design is changing. The emergence of service games on PC, mobile and console has created new expectations amongst consumers and requires new techniques from game makers. Lovell shows how service games require all the skills of product game development, and more. He provides a toolset for game makers of all varieties to create fun, profitable games. Filled with practical advice, memorable anecdotes and a wealth of game knowledge, the Pyramid of Game Design is a must-read for all game developers.